Hubungan maqasid syariah, usul fiqh & qawaed fiqhiyyah dalam penetapan hukum fekah semasa: analisis beberapa pandangan hukum dan fatwa terpilih dalam isu-isu halal - Ismail, Hasanuddin; Tuan Sidek, Tuan Muda (Universiti Malaysia Pahang, 2024)
Usul Fiqh, Qawaed Fiqhiyyah and Maqasid Shariah are three branches of knowledge which are usually associated with the process in determining a certain Islamic ruling. In relation to that, this paper is presented to discuss roles of these three branches and their relationship in the determination of contemporary Islamic rulings. There are similarities and differences among those three and often in term of application, misunderstandings arose. There is also a view that views opinions in the Syafie school are quite strict and need to be evaluated from the point of view of achieving maqasid shariah. Therefore, a relationship analysis was made on Islamic rulings in Malaysia in halal issues to see the extent to which the relationship of the three branches is implemented This study was conducted qualitatively. Data were collected and analyzed using the document analysis approach. The study found that these three branches have a close relationship particularly on Islamic rulings in halal issues in Malyasia. In fact, they complement each other. Every issued Islamic ruling must be in accordance with the principles and methods that have been outlined in those three branches. From the study, it is also noted that earlier jurists have established a well-organized methodology as a guide in the process of determination of certain Islamic law.